Phagocyte NADPH oxidase and specific immunity - Cachat, Julien; Deffert, Christine; Hugues, Stephanie; Krause, Karl-Heinz (Clinical science (1979), 2015)
The phagocyte NADPH oxidase NOX2 produces reactive oxygen species (ROS) and is a well-known player in host defence. However, there is also increasing evidence for a regulatory role of NOX2 in adaptive immunity. Deficiency in phagocyte NADPH oxidase causes chronic granulomatous disease (CGD) in humans, a condition that can also be studied in CGD mice. Clinical observations in CGD patients suggest a higher susceptibility to autoimmune diseases, in particular lupus, idiopathic thrombocytopenic purpura and rheumatoid arthritis. In mice, a strong correlation exists between a polymorphism in a NOX2 subunit and the development of autoimmune arthritis. NOX2 deficiency in mice also favours lupus development. Both CGD patients and CGD mice exhibit increased levels of immunoglobulins, including autoantibodies. Despite these phenotypes suggesting a role for NOX2 in specific immunity, mechanistic explanations for the typical increase of CGD in autoimmune disease and antibody levels are still preliminary. NOX2-dependent ROS generation is well documented for dendritic cells and B-lymphocytes. It is unclear whether T-lymphocytes produce ROS themselves or whether they are exposed to ROS derived from dendritic cells during the process of antigen presentation. ROS are signalling molecules in virtually any cell type, including T- and B-lymphocytes. However, knowledge about the impact of ROS-dependent signalling on T- and B-lymphocyte phenotype and response is still limited. ROS might contribute to Th1/Th2/Th17 cell fate decisions during T-lymphocyte activation and might enhance immunoglobulin production by B-lymphocytes. In dendritic cells, NOX2-derived ROS might be important for antigen processing and cell activation.